2020
DOI: 10.1371/journal.pone.0230400
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-binding proteins are altered in the cerebellum in schizophrenia

Abstract: Alterations in the cortico-cerebellar-thalamic-cortical circuit might underlie the diversity of symptoms in schizophrenia. However, molecular changes in cerebellar neuronal circuits, part of this network, have not yet been fully determined. Using LC-MS/MS, we screened altered candidates in pooled grey matter of cerebellum from schizophrenia subjects who committed suicide (n = 4) and healthy individuals (n = 4). Further validation by immunoblotting of three selected candidates was performed in two cohorts compr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 87 publications
(105 reference statements)
0
11
0
2
Order By: Relevance
“…However, a reduction in PC Parv immunoreactivity (Stepień et al, 2012) and cell size (Satoh et al, 1991) has been described in AD compared to controls. Decreases in PC Parv mRNA levels and Parv-ir neuron numbers occur in people with autism (Soghomonian et al, 2017), while an increase in cerebellar Parv levels were found in the schizophrenic brain (Vidal-Domènech et al, 2020). These observations indicate that Parv cells are vulnerable in various neurologic disorders, whereas Calb is associated with cellular resistance in the face of neuropathologic diseases (Fairless et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
“…However, a reduction in PC Parv immunoreactivity (Stepień et al, 2012) and cell size (Satoh et al, 1991) has been described in AD compared to controls. Decreases in PC Parv mRNA levels and Parv-ir neuron numbers occur in people with autism (Soghomonian et al, 2017), while an increase in cerebellar Parv levels were found in the schizophrenic brain (Vidal-Domènech et al, 2020). These observations indicate that Parv cells are vulnerable in various neurologic disorders, whereas Calb is associated with cellular resistance in the face of neuropathologic diseases (Fairless et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
“…We found that only 56 of the 250 altered proteins had been previously reported in a gene expression study in an iPSC model of SZ [ 28 ], and that only 16 altered proteins had been reported in a microarray assay in human cerebellum [ 25 ] ( Figure 1 E, Supplementary Dataset S2 ). Eighty-six altered proteins in the cerebellum had been previously reported as altered in other brain regions in SZ, and 20 proteins had been reported in two recent cerebellar proteomic studies [ 26 , 27 ] using different designs (sample pooling versus individual sample analyses), labelling of peptides (chemical labelling quantification versus label-free quantification), type of lysates (cellular fractioning versus whole extracts), mass spectrometry instruments (LTQ-Orbitrap XL, Thermofisher or DS-11, DeNovix versus Q-Exactive, Thermofisher) and age of SZ subjects, among others ( Table S2 and Supplementary Dataset S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the growing importance of the cerebellum as a stress target region highly vulnerable to accumulating molecular stress-induced errors in schizophrenia, only a few recent studies have investigated global mRNA [ 25 ] or proteomic alterations in this region [ 26 , 27 ]. The main aim of our study was to identify altered protein networks in the cerebellum with potential therapeutic targets for schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Various tissue samples have been used to date to study the proteomics of suicidal behaviour, including the prefrontal cortex[ 64 - 66 ], amygdala[ 65 ] and cerebellum[ 67 ]. Studies have also examined cerebrospinal fluid[ 68 , 69 ] and plasma[ 70 , 71 ], as although these are still invasive, they represent more easily accessible sources of tissue.…”
Section: Use Of -Omics In Research Into Suicidal Behaviourmentioning
confidence: 99%
“…A reoccurring pattern can be observed, that is similar to the other -omics studies described above. Here, too, there are connections with many of the previously mentioned cell functions and pathways, with indications of association with glial function, neurodegeneration, oxidative stress, neuronal injury[ 64 ], the cytoskeleton, synaptic functions[ 65 ], coagulation and inflammation[ 70 ], decreased glucose utilisation[ 69 ], altered cholesterol metabolism in deliberate self-harm[ 71 ], transport functions and cell communication in schizophrenia suicide victims[ 67 ], the GABA receptor signalling pathway, and pathways related to other neurotransmitters in mood disorder suicide victims ( e.g. , serotonin receptor signalling, melatonin signalling, CREB signalling in neurons, dopamine receptor signalling)[ 66 ].…”
Section: Use Of -Omics In Research Into Suicidal Behaviourmentioning
confidence: 99%